PERLINDUNGAN HUKUM WAJIB PAJAK TERHADAP SURAT KEPUTUSAN KEBERATAN DALAM SENGKETA PAJAK - Bisinglasi, Nadia Permata Ekasari (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
The effect of the law on the appeal by the taxpayer is by the issuance of the Decree of Objection, if in the Decree of Objection the taxpayer also still feel not satisfied then based on Laws of General Provisions of Taxation or UU KUP, the taxpayer is entitled to file the appeal back to the Tax Court. The legal effort of the taxpayer to seek justice becomes disconnected with the provisions of Article 33 paragraph (1) and Article 77 paragraph (1) of Law no. 14 year 2002 stating that the decision of the Tax Court is the final decision in examining and resolving tax disputes, so that no appeal or cassation can be appealed. This resulted in reduced taxpayers' right to seek justice. Allowable legal action is to conduct a Review, and this effort is extraordinary.